Perbandingan Kejadian Shivering Pasca Operasi Pada Pasien Dengan Anestesi Umum dan Pasien Dengan Spinal Anestesi - Suprapto, Suprapto; Elsi Jerau, Emiliani; Suandika, Made; Bisma Yudha, Magenda (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Postoperative shivering is a common physiological complication that occurs after surgical procedures, particularly in patients undergoing anesthesia. This condition can increase oxygen consumption, cardiac workload, and patient discomfort. This study aims to compare the incidence of postoperative shivering between patients receiving general anesthesia and those receiving spinal anesthesia. The research was conducted in the Operating Room of RS Tk. III Dr. Reksodiwiryo Padang using a descriptive analytic design with a quantitative approach. A total of 48 patients were selected through total sampling, consisting of 24 patients who received general anesthesia and 24 who received spinal anesthesia. Data were analyzed using the Chi-Square test and Fisher’s Exact Test.The results showed that postoperative shivering occurred more frequently in patients who received spinal anesthesia 23 respondents (95.8%) than in those who received general anesthesia 13 respondents (54.2%). Fisher’s Exact Test revealed a p-value of 0.002 (p < 0.05), indicating a statistically significant relationship between the type of anesthesia and the occurrence of postoperative shivering. This finding suggests that the type of anesthesia influences the risk of shivering, with spinal anesthesia posing a higher risk. Preventive measures, such as warming intravenous fluids and monitoring body temperature, are recommended—especially for patients undergoing spinal anesthesia